Determination of the activation energy of the reaction of photosynthesis in chlorophyll synthesizing microalgae - Dyachok, Vasyl; Katysheva, Viktoriia (Lviv Polytechnic Publishing House, 2016)
The dynamics of absorption of carbon dioxide at corresponding temperature by microalgae Chlorella was studied. The results of experimental research will allow to calculate the energy of activating photochemical reaction and other values of kinetics of increase of microalgae within the limits of the investigating temperatures. The analytical dependence of coefficient of growth biomass on temperature within the limits of the investigating temperature was established. The stages of transport of carbon dioxide from air to internal volume of microalgae cell was determined through literature. The optimal terms of their cultivation was selected and analyzed. The results showed that it is possible to forecast the technological scheme of cleaning of gas emissions from carbon dioxide by biological method.
Keywords: photosynthesis; microalgae; kinetics; biomass; chlorella; increment rate; carbon dioxide